The book of requiems from the earliest ages to the present period - Burn, David 1974-; Bergé, Pieter 1967- (Leuven University Press, 2022)
Volume I treats the Requiem's liturgical and chant background, the craft of early Requiem composition, and eight of the earliest composed Requiems, from c. 1450 to c. 1550.